2013
DOI: 10.2217/rme.13.12
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Controlled Automated Neural Differentiation of Mouse Embryonic Stem Cells

Abstract: SummaryAutomation and oxygen tension control are two tools, which provide significant improvements to the reproducibility and efficiency of stem cell productions processes. Aim:The aim of this study was to establish a novel automation platform capable of controlling oxygen tension during both the cell culture and liquid handling steps of neural differentiation processes. Materials and Methods: We built a bespoke automation platform, which enclosed a liquid handling platform in sterile, oxygen-controlled enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…3F). A decline in glucose consumption has been observed in mouse PSCs and mouse naïve PSC neural differentiation has been charted every 48 h (Fernandes et al, 2010;Mondragon-Teran et al, 2013); however, neither study contrasted mitochondrial metabolism with glycolytic metabolism, and both altered the medium base for neural inductions. Our findings establish the acquisition of a more quiescent metabolism upon PSC exit from pluripotency, in which carbohydrate utilization is halved by the NPC state.…”
Section: Glucose-derived Carbon Utilization Decreases With Nascent Ecmentioning
confidence: 99%
See 1 more Smart Citation
“…3F). A decline in glucose consumption has been observed in mouse PSCs and mouse naïve PSC neural differentiation has been charted every 48 h (Fernandes et al, 2010;Mondragon-Teran et al, 2013); however, neither study contrasted mitochondrial metabolism with glycolytic metabolism, and both altered the medium base for neural inductions. Our findings establish the acquisition of a more quiescent metabolism upon PSC exit from pluripotency, in which carbohydrate utilization is halved by the NPC state.…”
Section: Glucose-derived Carbon Utilization Decreases With Nascent Ecmentioning
confidence: 99%
“…Despite the clear profile of increasing quiescence during hPSC ectoderm differentiation, a sharp peak in metabolic parameters, including ROS, and a trough in pluripotency markers occurred within the first 24 h of differentiation. This metabolic exit event has been missed by other metabolic assessments of differentiation that only assess every 48 h or longer (Cho et al, 2006;Fernandes et al, 2010;Prigione and Adjaye, 2010;Varum et al, 2011;Mondragon-Teran et al, 2013). Similar to the waves of transcriptional and proteomic remodeling that take place during reprogramming to iPSCs (Hansson et al, 2012;Polo et al, 2012), this metabolic exit event may be necessary to shift PSCs out of their stable primed state (Enver et al, 2009), thus marking the onset of differentiation.…”
Section: Npc Induction Reduces Mitochondrial Activity and Investmentmentioning
confidence: 99%
“…In contrast, others revealed that hypoxia promoted differentiation of human ESCs into cardiomyocytes [48] and chondrocytes [49]. Hypoxia also promoted mouse ESCs to differentiate to neurons [50], endothelial cells, and hematopoietic stem cells [51]. These apparently controversial reports on the effect of hypoxia on differentiation may be explained by the stage of stemness at which the hypoxia was introduced, and the duration and degree of hypoxia.…”
Section: Hypoxia and Hifs In Embryonic Stem Cells And Induced Pluripomentioning
confidence: 99%